MRI appearance of chronic subdural hematoma - Hasan, Dimah; Nikoubashman, Omid; Pjontek, Rastislav; Stockero, Andrea; Hamou, Hussam Aldin; Wiesmann, Martin (Frontiers in Neurology, 2022)
Objective: Our aim was to describe the MRI characteristics of chronic subdural hematoma (cSDH) and to ascribe MRI patterns. Methods: Twenty patients with a total of 27 subdural hematomas underwent contrast enhanced MRI of the brain at our institution between April 2019 and May 2021. The images were independently evaluated by two experienced neuroradiologists with regards to imaging characteristics on T1w, T2w, T2*-GRE, FLAIR, DWI, and contrast-enhanced images. Results: The signal characteristics of cSDH on T1- and T2-weighted images were rather heterogeneous. The majority of hematomas (74%) had internal septations. Surprisingly, contrast enhancement along the outer membrane adjacent to the cranium was noticed in all hematomas. There was also contrast enhancement along the inner membrane adjacent to the brain in more than one third of the hematomas (37%). In approximately two thirds of the cSDH (62%), there was a mass-like enhancement of the hematoma. Most hematomas (89%) were partially hypointense on T2*-GRE and/or SWI. Restricted diffusion was detected in approximately one third of the hematomas (33%). Conclusion: Consistent contrast enhancement along the outer membrane, triangular-shaped contrast enhancement at the borders of the cSDH and infrequent enhancement of the inner membrane may help to distinguish cSDH from other entities such as empyema and tumors. Mass-like enhancement may refer to non-solid hematomas and could be an indicator for hematoma growth and a possible surrogate for successful endovascular embolization. Restricted diffusion in a subdural mass is not specific for empyema but may also be found in cSDH.